2021
DOI: 10.1038/s41467-020-20357-z
|View full text |Cite
|
Sign up to set email alerts
|

ZBP1 promotes LPS-induced cell death and IL-1β release via RHIM-mediated interactions with RIPK1

Abstract: Inflammation and cell death are closely linked arms of the host immune response to infection, which when carefully balanced ensure host survival. One example of this balance is the tightly regulated transition from TNFR1-associated pro-inflammatory complex I to pro-death complex II. By contrast, here we show that a TRIF-dependent complex containing FADD, RIPK1 and caspase-8 (that we have termed the TRIFosome) mediates cell death in response to Yersinia pseudotuberculosis and LPS. Furthermore, we show that cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 39 publications
6
63
0
2
Order By: Relevance
“…A recent study reported a cell death complex containing FADD, RIPK1 and CASP8 which is triggered by TRIF signaling (referred to as the “TRIFosome”). This complex is critically involved in the cell death induced by LPS when TAK1 is inhibited [137] . Although the physical presence of TRIF in a complex with other death molecules has not been shown, it is possible that TRIF can participate in PANoptosome formation through its RHIM domain.…”
Section: Assembly Of the Panoptosome: Interaction Network Of Panoptosome Componentsmentioning
confidence: 99%
“…A recent study reported a cell death complex containing FADD, RIPK1 and CASP8 which is triggered by TRIF signaling (referred to as the “TRIFosome”). This complex is critically involved in the cell death induced by LPS when TAK1 is inhibited [137] . Although the physical presence of TRIF in a complex with other death molecules has not been shown, it is possible that TRIF can participate in PANoptosome formation through its RHIM domain.…”
Section: Assembly Of the Panoptosome: Interaction Network Of Panoptosome Componentsmentioning
confidence: 99%
“…TRAM is necessary for the endosomal trafficking of TRIF, during which it forms secondary signaling complexes (Kagan et al, 2008), including Complex II. ZBP1 is another RHIM-containing protein that plays many critical roles, including promoting the formation of RIPK1-dependent Complex II under pyroptotic conditions and initiation of an alternative RIPK1 signaling pathway by engaging RIPK3 directly in response to Z-forms of nucleic acids upon viral infection (Muendlein et al, 2021;Zhang et al, 2020).…”
Section: Alternative Methods Of Immunoprecipitation Of Ripk1 and Other Complex-ii-related Factorsmentioning
confidence: 99%
“…For example, it is not well established whether an analog of Complex I forms in TRIF pathway, and at what level(s) some of the inhibitory events observed in TNFR1 Complex I, such as RIPK1 ubiquitination and phosphorylation by cIAP1/2, LUBAC, TAK1, and the IKK complex, occur in the TRIF‐mediated signaling pathway. However, it is clear that TLR signaling also involves the formation of a large, detergent‐insoluble Complex II responsible for initiating cell death (Muendlein et al., 2021; Muendlein et al., 2020; Najjar et al., 2016; Saleh et al., 2017). Beside regulating cell death, RIPK1 and RIPK3 in Complex II also promote inflammatory gene transcription and translation, contributing, along with the danger‐associated molecular patterns (DAMPs) released by lysed cells, to the inflammatory nature of TLR‐induced cell death.…”
Section: Commentarymentioning
confidence: 99%
“…RIPK1 autophosphorylation at S166 regulates the kinase activity, but it cannot impose conformational changes on RIPK1 to activate the downstream cell death signaling (Laurien et al, 2020 (Dondelinger et al, 2015;Koppe et al, 2016;Geng et al, 2017;Jaco et al, 2017;Menon et al, 2017;Lafont et al, 2018). Recent studies have suggested that ZBP1 promotes caspase-8-mediated cell death and inflammasome activation by RHIM-mediated interactions with RIPK1, which depends on the kinase activity of RIPK1 (Muendlein et al, 2021). The kinase-independent and scaffold-like functions of RIPK1, which mediates NF-κB and MAPK activation, are essential for cell survival.…”
Section: Complex Network Among Related Molecules Of Necroptosismentioning
confidence: 99%
“…However, phosphorylation of RIPK1 by kinases, including MAPK-activated protein kinase 2 (MK2) that phosphorylates RIPK1 at Ser321/336, TAK1 that phosphorylates RIPK1 at Ser321, NF-κB kinases (IKKs) that phosphorylate RIPK1 on multiple residues, TANK binding kinase 1 (TBK1), and IkappaB kinase epsilon (IKKε), results in the inhibition of RIPK1 kinase activity and prevents TNF-mediated RIPK1-dependent cell death ( Dondelinger et al, 2015 ; Koppe et al, 2016 ; Geng et al, 2017 ; Jaco et al, 2017 ; Menon et al, 2017 ; Lafont et al, 2018 ). Recent studies have suggested that ZBP1 promotes caspase-8-mediated cell death and inflammasome activation by RHIM-mediated interactions with RIPK1, which depends on the kinase activity of RIPK1 ( Muendlein et al, 2021 ).…”
Section: Complex Network Among Related Molecules Of Necroptosismentioning
confidence: 99%